2010
DOI: 10.1039/c0cc01071e
|View full text |Cite
|
Sign up to set email alerts
|

Chiral gold nanoparticle-based electrochemical sensor for enantioselective recognition of 3,4-dihydroxyphenylalanine

Abstract: The enantioselective recognition of 3,4-dihydroxyphenylalanine using penicillamine-modified gold nanoparticles has been investigated. Smaller gold nanoparticles with one enantiomeric ligand facilitate the redox reaction of only one enantiomer of 3,4-dihydroxyphenylalanine, with cross inversion for the gold nanoparticles with the other enantiomeric ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 19 publications
1
98
0
Order By: Relevance
“…The use of chiral ligands in the proximity of nanoclusters and nanoparticles has already led to the synthesis of important novel nanomaterials with individual dissymmetry, such as intrinsically chiral nanoparticles [54,55], capped nanocrystals with a chiral distribution of the electron density [61,75], and footprinted nanoparticles [64,65]. Although still in their infancy, these systems have shown very high catalytic activity and enantioselectivity toward several organic transformations [66,143], and can be considered potential electrochemical [144], VCD [57], and SEROA (surface enhanced Raman optical activity) [145] sensors. However, the potential uses of nanoparticles with individual chirality as a plasmonic material [52,76] is still hindered primarily due to limitations in colloidal synthesis.…”
Section: Discussionmentioning
confidence: 98%
“…The use of chiral ligands in the proximity of nanoclusters and nanoparticles has already led to the synthesis of important novel nanomaterials with individual dissymmetry, such as intrinsically chiral nanoparticles [54,55], capped nanocrystals with a chiral distribution of the electron density [61,75], and footprinted nanoparticles [64,65]. Although still in their infancy, these systems have shown very high catalytic activity and enantioselectivity toward several organic transformations [66,143], and can be considered potential electrochemical [144], VCD [57], and SEROA (surface enhanced Raman optical activity) [145] sensors. However, the potential uses of nanoparticles with individual chirality as a plasmonic material [52,76] is still hindered primarily due to limitations in colloidal synthesis.…”
Section: Discussionmentioning
confidence: 98%
“…L-type enantiomer oen exhibits positive CD signal at 220 nm, and D-type enantiomer always has negative CD signal. 13 The CD results suggested that L-Dopa could absorb on L-Cys-capped AuNPs whereas D-Dopa did not adsorb on L-Cys-capped AuNPs. The results agreed with the change of L-Dopa (or D-Dopa) content in the supernatant, and the reduction of L-Dopa in the supernatant was attributed to the fact that L-Cys-capped AuNPs could bind L-Dopa.…”
Section: Chiral Recognition Mechanismmentioning
confidence: 95%
“…The chirality of gold nanoparticles has recently become an intensively studied field of modern nanoscience as it opens new possibilities in catalysis and sensing applications8910. The use of plasmon resonances in chiral metamaterials has been discussed and employed in several examples1112131415.…”
mentioning
confidence: 99%